The Impact of Job Insecurity on Turnover Intention with Work Motivation as Moderation - Bethari Taufiqah Syifa; Candra Vionela Merdiana (International Journal of Economics and Management Research, 2025)
This research explores the impact of job insecurity on turnover intention among Generation Z employees in Yogyakarta, with work motivation examined as a moderating factor. Employing a quantitative methodology, data were gathered from participants and analyzed using Partial Least Squares (PLS). The analysis indicates that job insecurity has a significant positive effect on turnover intention, whereas work motivation mitigates this relationship. The results highlight the importance of fostering work motivation as a strategic approach for organizations to reduce employee turnover intention.